Enhancement of Silymarin Anti-fibrotic Effects by Complexation With Hydroxypropyl (HPBCD) and Randomly Methylated (RAMEB) β-Cyclodextrins in a Mouse Model of Liver Fibrosis - Gharbia, Sami; Balta, Cornel; Herman, Hildegard; Rosu, Marcel; Váradi, Judit; Bácskay, Ildikó; Vecsernyés, Miklós; Gyöngyösi, Szilvia; Fenyvesi, Ferenc; Voicu, Sorina N.; Stan, Miruna S.; Cristian, Roxana E.; et al. (Frontiers in Pharmacology, 2018)
Silymarin (Sy) shows limited water solubility and poor oral bioavailability. Water-soluble hydroxypropyl (HPBCD) and randomly methylated (RAMEB) β-cyclodextrins were designed to enhance anti-fibrotic efficiency of silymarin in CCl4-induced liver fibrosis in mice. Experimental fibrosis was induced by intraperitoneal injection with 2 ml/kg CCl4 (20% v/v) twice a week, for 7 weeks. Mice were orally treated with 50 mg/kg of Sy-HPBCD, Sy-RAMEB and free silymarin. For assessment of the spontaneous reversion of fibrosis, CCl4 treated animals were investigated after two weeks of recovery time. The CCl4 administration increased hepatic oxidative stress, augmented the expression of transforming growth factor-β1 (TGF-β1) and Smad 2/3, and decreased Smad7 expression. Furthermore, increased α-smooth muscle actin ( -SMA) expression indicated activation of hepatic stellate cells (HSCs), while up-regulation of collagen I (Col I) and matrix metalloproteinases (MMPs) expression led to an altered extracellular matrix enriched in collagen, confirmed as well by trichrome staining and electron microscopy analysis. Treatment with Sy-HPBCD and Sy-RAMEB significantly reduced liver injury, attenuating oxidative stress, restoring antioxidant balance in the hepatic tissue, and significantly decreasing collagen deposits in the liver. The levels of pro-fibrogenic markers' expression were also significantly down-regulated, whereas in the group for spontaneous regression of fibrosis, they remained significantly higher, even at 2 weeks after CCl4 administration was discontinued. The recovery was significantly lower for free silymarin group compared to silymarin/β cyclodextrins co-treatments. Sy-HPBCD was found to be the most potent anti-fibrotic complex. We demonstrated that Sy-HPBCD and Sy-RAMEB complexes decreased extracellular matrix accumulation by inhibiting HSC activation and diminished the oxidative damage. This might occur via the inhibition of TGF-β1/Smad signal transduction and MMP/tissue inhibitor of MMPs (TIMP) rebalance, by blocking the synthesis of Col I and decreasing collagen deposition. These results suggest that complexation of silymarin with HPBCD or RAMEB represent viable options for its oral delivery, as a potential therapeutic candidate, with applications in the treatment of liver fibrosis.